Penggunaan Media Sosial Pada Second Account Instagram Mahasiswa FISIP Universitas Jember: Perspektif Dramaturgi - Sri Devi Januarifka Fitria; Diah Firlia Khumairoh; Halimatuz Zahro (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The presence of globalization accompanied by an increasingly sophisticated technological advancement has increased the need for information. Social media is one of the technological developments that has advances in the field of communication. With social media, users can communicate two-way online. In addition, social media is also often used by users as an identity building or online self-profile so that it can be recognized by other users in other parts of the world. A very popular social media used by teenagers is Instagram. Instagram is a social media platform used to share moments or channel expressions. This research has the aim of knowing how they express themselves on the second account of Instagram, considering that they upload themselves more often on the second account than on the first account. In analyzing this research using qualitative methods and dramaturgy theory that explains about the front stage and back stage. The results showed that the first account as a front stage because users maintain their image by limiting Instagram posts, while the second account as a back stage is used to express their true identity without any imaging.